Soil greenhouse gas emissions and their relations to soil attributes in a sugarcane area - Bicalho, Elton da Silva [UNESP] (2016)
The production of the main soil greenhouse gases (GHG: CO2, CH4 and N2O) is influenced by agricultural practices that causes changes in soil phys¬ical, chemical and biological attributes, directly affecting their emission to the atmos¬phere. The aim of this study was to investigate the infield soil CO2 emissions (FCO2) and the soil CO2, CH4 and N2O production potentials (PCO2, PCH4 and PN2O, respec¬tively) in laboratory conditions, and their relationship to soil attributes in a mechanically harvested sugarcane area. The experimental area consisted of a 50 × 50-m radially symmetrical grid containing 133 points spaced at minimum distances of 0.5 m in the center of the sample grid. It was carried out eight evaluations of FCO2, soil temperature and soil moisture over a period of 19 days. Soil physical and chemical attributes were determined by sampling at a depth of 0–10 cm. The quantification of PCO2, PCH4 and PN2O consisted of laboratory incubation and determination of gas concentration by gas chromatography. FCO2 presented an infield average emission value of 1.19 µmol CO2 m−2 s−1, while GHG production in laboratory was 2.34 µg C–CO2 g−1 d−1 and 0.20 ng N–N2O g−1 d−1 for PCO2 and PN2O, respectively. No significant production or oxidation was observed for CH4. The factor analysis showed the formation of two independent processes that explained almost 72% of the total variance observed in the data. The first process was related to the transport of FCO2 and its relation to soil physical attrib¬utes, such as microporosity, macroporosity, the C/N ratio, soil moisture and soil bulk density, showing the dependence between FCO2 and soil porosity. The second process was related to the soil CO2 and N2O production potentials in laboratory conditions and their relation to soil chemical attributes, such as sum of bases, pH and available phos¬phorus, which affects the microbial activity and contributes to the GHG production. Although presented as independent, these processes are coupled and occur simulta¬neously in the soil, in addition to provide information about their variability, showing if the infield emissions are due to the gas transport processes or to soil carbon levels and their quality. Furthermore, the spatial dependence of FCO2 is related to soil poros¬ity, as well as the spatial dependence of PCO2 and PN2O is related to soil chemical attributes. In addition, anisotropy occurred mainly under infield conditions, mostly for the attributes related to soil porosity since disturbed soils used under laboratory con-ditions lose their structure and hence the effect of the management found under infield conditions.